Maize benefits the predatory beetle, Propylea japonica (Thunberg), to provide potential to enhance biological control for aphids in cotton. - Fang Ouyang; Xingyuan Men; Bing Yang; Jianwei Su; Yongsheng Zhang; Zihua Zhao; Feng Ge (PLoS ONE, 2012)
Biological control provided by natural enemies play an important role in integrated pest management. Generalist insect predators provide an important biological service in the regulation of agricultural insect pests. Our goal is to understand the explicit process of oviposition preference, habitat selection and feeding behavior of predators in farmland ecosystem consisting of multiple crops, which is central to devising and delivering an integrated pest management program.The hypotheses was that maize can serve as habitat for natural enemies and benefits predators to provide potential to enhance biological control for pest insects in cotton. This explicit process of a predatory beetle, Propylea japonica, in agricultural ecosystem composed of cotton and maize were examined by field investigation and stable carbon isotope analysis during 2008-2010.Field investigation showed that P. japonica adults will search host plants for high prey abundance before laying eggs, indicating indirectly that P. japonica adults prefer to inhabit maize plants and travel to cotton plants to actively prey on aphids. The δ(13)C values of adult P. japonica in a dietary shift experiment found that individual beetles were shifting from a C(3)- to a C(4)-based diet of aphids reared on maize or cotton, respectively, and began to reflect the isotope ratio of their new C(4) resources within one week. Approximately 80-100% of the diet of P. japonica adults in maize originated from a C(3)-based resource in June, July and August, while approximately 80% of the diet originated from a C(4)-based resource in September.Results suggest that maize can serve as a habitat or refuge source for the predatory beetle, P. japonica, and benefits predators to provide potential to enhance biological control for insect pests in cotton.